Cultural dimensions of individualism and collectivism and risk of opioid misuse: A test of Social Cognitive Theory. Issue 11 (26th July 2022) - Kim, Shin Ye; Park, Sung Yong; Mathai, Babetta; Daheim, Jacob; France, Christopher; Delgado, Betsaida
Abstract: Background: Despite the critical role social and cultural contexts play in pain experience, limited theoretical and empirical attention has been devoted to the interplay between social, cognitive, cultural, and psychological factors in chronic pain management and the risk of opioid misuse. Methods: Using structural equation modeling, the present study tested the Social Cognitive Theory (SCT) of chronic pain management and risk of opioid misuse in the context of intraindividual cultural dimensions of individualism and collectivism among 316 ethnically diverse adults with chronic pain in the United States. Results: Social cognitive predictors account for a significant amount of variance in pain dysfunction and risk of opioid misuse in adults with chronic pain. Satisfaction with pain support was positively associated with both greater pain acceptance and greater pain self‐efficacy. Individualism was found to be positively associated with satisfaction with pain support, pain self‐efficacy, and pain acceptance but negatively associated with the risk of opioid misuse. Collectivism was positively associated with the risk of opioid misuse. Conclusions: The study findings not only empirically support using SCT for adults with chronic pain, but also provide a more thorough conceptual framework that highlights the intracultural diversity and interplay among social, cognitive, and psychological factors that affect pain experience and the risk of opioid misuse among adults with chronic pain.